Effects of a group-based music imagery program on promoting coping resources among undergraduate students: a pilot randomized controlled trial - Cheng, Winnie Lai Sheung; Wong, Lokki Lok-Ki (Frontiers in Psychology, 2023)
Background Music is well-known for its stress-reducing effects. Little is known about the potential effect of music interventions in fostering internal coping resources for stress management among undergraduate students in Hong Kong. Objectives This pilot study aimed to examine the efficacy of the Group-based Focus Music Imagery Program (GFMI) in promoting a stress-is-enhancing mindset, sense of coherence, and self-compassion among undergraduate students. Methods We used a two-arm parallel randomized controlled trial (RCT). The experimental arm received 6 weeks of GFMI with measures taken at two time points after completing baseline assessments (Weeks 6, 10). The control arm received 6 weeks of an active control program and completed the outcome measures at time points similar to the GFMI group. Data were collected using the Chinese versions of the Sense of Coherence Scale (C-SOC-13), the Self-Compassion Scale-Short Form (C-SCS-SF), the Stress Mindset Measure (C-SMM), the Perceived Stress Scale (C-PSS-10), and the Generalized Anxiety Disorder scale (C-GAD-7). Results Sixty-four participants were randomly assigned to either the experimental group (n = 32) or the control group (n = 32) between July 2021 and September 2022. The experimental group exhibited a retention rate of 71.9% at T1 (23 out of 32 participants), which slightly decreased to 65.6% (21 out of 32) at T2. The control group displayed a retention rate of 75% (24 out of 32) at T1, which dropped to 43.8% (14 out of 32) at T2. The GEE analyses showed insignificant differences between groups at any time point in C-SOC-13, C-SCS-SF, and C-SMM. Instead, the control group had a higher reduction in stress scores (C-PSS-10) at T1, and anxiety (C-GAD-7) at T2 than the experimental group. Conclusion The pilot trial provided valuable information in examining the feasibility of the trial design and intervention. Future studies with larger samples are needed to validate if GFMI can reliably promote coping resources to manage stress and anxiety in undergraduate students. Trial registration number https://www.researchregistry.com/, researchregistry8209.